Case Report: Multiple Chromosomal Translocations Including Novel CIITA-CREBBP Fusion and Mutations in a Follicular Lymphoma - Wang, Huan-You; Sokol, Ethan S.; Goodman, Aaron M.; Feldman, Andrew L.; Mulroney, Carolyn M. (Frontiers in Oncology, 2021)
The pathogenesis of follicular lymphoma is a multi-step process, in which chromosomal translocation between immunoglobulin heavy chain (IgH) and anti-apoptotic B-cell lymphoma 2 (BCL2), namely IgH-BCL2, is an earliest step, followed by other genetic/genomic alterations including but not limited to mutation of CREB binding protein (CREBBP). MHC class II transactivator (CIITA) is a transcription regulator responsible for expression of MHC class II molecules including HLA-DR in human. We report herein a novel fusion gene involving CIITA and CREBBP in a patient with a low-grade follicular lymphoma (FL) but with high Ki-67 proliferation index. In addition, our patient also harbors CREBBP mutation. Together, we postulate that total loss of CREBBP function may contribute, in part, to the lymphoma genesis. Furthermore, this patient has addition rare (TBL1XR1-TP63) and common (IgH-BCL2) chromosomal translocations and multiple mutations including BCL2, BRAF, MUTYH, and STAT6.